Estudo das propriedades estruturais, ferroicas e multiferroicas de compostos baseados no AlFeO3 - Santos, Guilherme Maia (2015)
It is still a challenging problem to obtain technologically useful materials displaying strong magnetoelectric coupling at room temperature. In the search for new effects and materials to achieve this kind of coupling, the study of nonlinear magnetoelectric effect has been proposed in the magnetically disordered relaxor ferroelectric materials. In this context, the aluminum iron oxide (AlFeO3), at room temperature ferroelectric relaxor and magnetic spin glass compound, emerges as an attractive lead-free magnetoelectric material along with nonlinear magnetoelectric effects. The AlFeO3-based compounds are attractive multiferroic materials, as those present piezoelectricity and ferrimagnetism at low temperatures. In this work the synthesis and ferroic properties of AlFeO3-based ceramics were investigated. Stoichiometric proportions of the precursors Fe2O3 and _Al2O3 - were milled and sintered to obtain AlFeO3 ceramics. Also, AlFeO3 ceramics doped with 2 % of Nb2O5 or MnO2 were sintered in oxygen atmosphere at 1450 0C. We present the structural studies of the AlFeO3 compound using the X-Ray diffraction data with Rietveld refinement method plus maximum entropy method and the first principle studies of the structural and electronic properties based on Density Functional Theory using the Siesta code. Following the combination of these two techniques, the analysis of the behavior of the structural, electric and magnetic properties of this system were made. Dielectric, pyroelectric and magnetic investigations suggested a magnetoelectric coupling between the electric and magnetic orderings at temperatures below _ 220 K for AlFeO3, AlFe0.98Mn0.02O3 and AlFe0.98Nb0.02O3, where the compositions show the ferromagnetic and ferroelectric ordering. The magnetoelectric coefficient behavior as a function of Hbias suggests a room temperature nonlinear magnetoelectric coupling in both single-phase and Nb-doped AlFeO3-based ceramic compositions